A Zn0.5Cd0.5S Photocatalyst Modified by 2D Black Phosphorus for Efficient Hydrogen Evolution from Water. Issue 19 (21st August 2018) - Zhao, Haitao; Liu, Heyuan; Sun, Ranran; Chen, Yanli; Li, Xiyou
Abstract: In this work, a photocatalyst composited of Zn0.5 Cd0.5 S and 2D black phosphorus (BP) nanosheets was successfully constructed for high‐efficient hydrogen evolution. The structure, morphology and chemical composition of BPx /Zn0.5 Cd0.5 S photocatalysts were characterized by X‐ray diffraction (XRD), high‐resolution transmission electron microscopy (HRTEM), atomic force microscopy (AFM), and X‐ray photoelectron spectroscopy (XPS). Remarkably, the hydrogen production rate of optimal BP15.2 /Zn0.5 Cd0.5 S nanocomposite achieves as high as 137.17 mmol/g/h under visible light irradiation (λ>420 nm), which is 5 times of that of pristine Zn0.5 Cd0.5 S. The corresponding apparent quantum efficiency (QE) is measured to be 36.3 % at 420 nm. Moreover, the hydrogen production rate reaches 26.96 mmol/g/h for BP15.2 /Zn0.5 Cd0.5 S under the irradiation of light with wavelength longer than 510 nm. The improved photocatalytic activity can be attributed to the interfacial contact between BP and Zn0.5 Cd0.5 S, which efficiently promotes electron‐hole pair separation. Moreover, 2D black phosphorus has successfully extended the absorption spectrum of BPx /Zn0.5 Cd0.5 S to the wavelength longer than 510 nm. Our result highlights the significance of BP as co‐catalyst in the development of new photocatalysis for hydrogen production from water. Abstract : Phosphorous is the new black : Zn0.5 Cd0.5 S loaded with black phosphorus co‐catalyst showed remarkably improved catalytic activity for hydrogen evolution.